Images of “We” and “They” in the Armenian Epic - Zakaryan, Seyran (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
In the article, it is shown that differences in the characters of “We” and “They” in the Armenian Epic are manifested in their mentality and behavioral attitudes towards visionaries and values (homeland, state, power, human, faith, etc.). In the Armenian Epic, the characters of “We” and “They” are generally presented in accordance with the “classic rules”: “We” are attributed with positive and “They” are attributed with negative features, but these attributions are not conditioned by their racial, tribal and religious specifics, but rather by the moral-anthropological ones. There is no hatred towards the enemy and there is no xenophobia. Negative traits are attributed to the representatives of the Enemy which, though in the general context of the relationship between “We” and “They” make their characters not hateful and despicable, but on the contrary,in some sense, outstanding and praiseworthy. For instance, in the epic in contrast to the Armenians, who rethink the reality by means of moral concepts, protect the homeland through heroes-saviors and do not have a vision of a state establishment and the wish to acquire the Enemy’s country after the victory, the Enemy for whom the morality naturally is a realization of the will of power, is represented as the holder of statehood attributes (state, state institutions, governor-hero, advisors, court, army, state interest and thinking, will of power), who instinctively tries strengthen his own state by conquering the others and prefers state interest to private.
Keywords: Armenian Epic, characters of “We” and “They”, Enemy, heroes, identity, National values, mental set, behaviour, norms of morality